2005
DOI: 10.1097/00008469-200504000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity evaluation of electromagnetic fields generated by 835-MHz mobile phone frequency band

Abstract: It is still unclear whether the exposure to electromagnetic fields (EMFs) generated by mobile phone radiation is directly linked to cancer. We examined the biological effects of an EMF at 835 MHz, the most widely used communication frequency band in Korean CDMA mobile phone networks, on bacterial reverse mutation (Ames assay) and DNA stability (in vitro DNA degradation). In the Ames assay, tester strains alone or combined with positive mutagen were applied in an artificial mobile phone frequency EMF generator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…One hundred three-day-old adult female flies were located in the 100 mm Petri dish with a wet filter paper to maintain humidity and exposed in the Wave Exposure V10 device (Patent No.0311892, Republic of Korea) [Chang et al, 2005]. This device produced 835 MHz SAR 1.6 W/kg or 4 W/kg EMF based on the transverse electromagnetic wave theory (Fig.…”
Section: Emf Exposure and Viability Testmentioning
confidence: 99%
See 2 more Smart Citations
“…One hundred three-day-old adult female flies were located in the 100 mm Petri dish with a wet filter paper to maintain humidity and exposed in the Wave Exposure V10 device (Patent No.0311892, Republic of Korea) [Chang et al, 2005]. This device produced 835 MHz SAR 1.6 W/kg or 4 W/kg EMF based on the transverse electromagnetic wave theory (Fig.…”
Section: Emf Exposure and Viability Testmentioning
confidence: 99%
“…Ames test and DNA stability assay show that 835 MHz electromagnetic field (EMF) does not increase the mutation frequency or DNA degradations [Chang et al, 2005]. In Caenorhabditis elegans, 750 MHz electromagnetic radiation activates the hsp16 > GFP transgene in which the GFP reporter gene is controlled by the hsp16 promoter [de Pomerai et al, 2000].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrary, other studies failed to prove any contribution of EMR on cellular DNA damage. Hook, et al [44] found that there was not any significant effect of EMR on T lymphoblastoid cells, EMR neither affected the reverse mutation frequency nor accelerated DNA degradation [45]. Others had previously proved that 2450 MHz irradiation does not appear to cause DNA damage in cultured mammalian cells [46].…”
Section: Discussionmentioning
confidence: 99%
“…The scientific evidence shows that mobile phones emit electromagnetic radiation (radiofrequency, RF) that is essentially non-ionizing. (frequencies between 300 MHz and 300 GHZ) [56][57][58]. The specific absorption rate (SAR) measures the energy dose that subjects exposed to RF absorb and is expressed in power (watts) by tissue mass (kilograms) [W/kg].…”
Section: Background Knowledgementioning
confidence: 99%